The implementing of progressive PjBL in elementary school: A case study of SDU Permata Muhammadiyah 5 of Malang - Heri Sulistyono; Nurul Zuriah; Endang Poerwanti; Agus Tinus (Research and Development in Education (RaDEn), 2025)
The implementation of progressive PjBL as a learning model that presents contextual problems has progressively undergone many developments according to the context and unique characteristics of each school. This study aims to analyze the implementation of the values ​​of the progressive Islamic message in PjBL at Permata Mulia Elementary School (SDU). This study used a qualitative descriptive research method with a case study approach. The results show that the integration and implementation of progressive PjBL through progressive Islamic message (RIB) was successfully implemented through three main stages: planning, implementation, and evaluation. Each learning stage is designed to instill Islamic values, build creativity, and foster critical and collaborative thinking skills. The integration of Progressive Islamic principles strengthens the holistic and meaningful learning process. However, implementation faces various challenges, such as the diversity of student characters, limited facilities, and the need to improve teacher competency and parental participation. Therefore, adaptive and collaborative strategies are needed at all levels—teachers, schools, and parents—so that RIB-based PjBL can become a strategic instrument in shaping a generation of learners who are faithful, knowledgeable, and charitable.